2019
DOI: 10.1158/0008-5472.can-18-3394
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Sensitizes MGMT-Deficient Tumor Cells to ATR Inhibitors

Abstract: O 6-methylguanine-DNA methyltransferase (MGMT) is an enzyme that removes alkyl groups at the O 6-position of guanine in DNA. MGMT expression is reduced or absent in many tumor types derived from a diverse range of tissues, most notably in glioma. Low MGMT expression confers significant sensitivity to DNA alkylating agents such as temozolomide (TMZ), providing a natural therapeutic index over normal tissue. In this study, we sought to identify novel approaches which could maximally exploit the therapeutic index… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 17 publications
(24 reference statements)
4
47
2
Order By: Relevance
“…Historically, these tumors have been treated with maximal surgical resection, followed by external beam radiation therapy. Survival was extended by adding the alkylator temozolomide (TMZ) ( Arora and Somasundaram, 2019 ; Jackson et al., 2019 ; Nam and de Groot, 2017 ; Thomas et al., 2017 ; Zhang et al., 2012b ). Surgery followed by concurrent chemo-radiation remain the standard of care for patients with GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, these tumors have been treated with maximal surgical resection, followed by external beam radiation therapy. Survival was extended by adding the alkylator temozolomide (TMZ) ( Arora and Somasundaram, 2019 ; Jackson et al., 2019 ; Nam and de Groot, 2017 ; Thomas et al., 2017 ; Zhang et al., 2012b ). Surgery followed by concurrent chemo-radiation remain the standard of care for patients with GBM.…”
Section: Introductionmentioning
confidence: 99%
“…While the clinical significance of STAG2 deficiency in human cancers remains under investigation, preclinical data have shown a synthetic lethality conferred by STAG2 mutations with DNA DSB repair genes, including increased sensitivity to PARP and ATR inhibitors 6,27 . This has been previously studied in other biomarkers of defective DNA damage repair, including IDH1/2 mutational status and MGMT promoter methylation [28][29][30] . On the other hand, STAG2 deficient cancer cells have also been shown to exhibit increased sensitivity in vitro to ionizing radiation and traditional chemotherapeutic agents, including temozolomide 6 , which contrasts with the aggressive clinical course of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to determine the role of methylation status of MGMT and DDR genes in DDR inhibitor clinical trials. For example, TMZ preferentially sensitizes MGMT-deficient tumor cells to ATR inhibition in preclinical models, 46 but similar observations have not been described with DNA-PK or ATM inhibition. We recommend inclusion of both MGMT promoter methylated and unmethylated GBM tumors in early phase clinical trials and to stratify based on MGMT status in order to detect early signals regarding the role of MGMT status in determining response to DDR inhibitors.…”
Section: Strategies For Successful Clinical Development Of Ddr Inhibimentioning
confidence: 93%
“… 45 Jackson et al demonstrated that TMZ activated ATR in an MGMT-dependent manner and that treatment of MGMT-deficient cells with TMZ increased sensitivity to ATR inhibitors in in vitro and in vivo models of GBM cell lines. 46 The role of MGMT promoter methylation status in determining response to DDR inhibitors needs to be investigated further in clinical trials.…”
Section: Atr Inhibitorsmentioning
confidence: 99%